Green Sabo Application for Erosion Control in Upper Land Area - Moh. Dedi Munir (Jurnal Teknik Hidraulik)
Erosion and sedimentation on the upstream river flow area have caused various problems along the Citarum River in West Java. Many parties, both governmental and private, have and should continue to make various efforts to overcome the problem both in the form of technical and non technical control in all parts of the river basin both upstream and downstream. Sedimen control in the upstream land area is one method developed because this way directly reduces the erosion at the exact location. The physical model of green sabo technique in area is an example of a test run for erosion control in the upstream region by demonstration plot. This method uses the treatment of green sabo technique that is straw method, coco fiber net, mulch, and natural treatment. The purpose of model implementation is to measure and compare the rate of erosion of various treatments as mentioned earlier. Based on calculations in the field consisting of soil compilers, rain, and slope, it is known that the straw method is the best treatment medium in controlling erosion on the land area. The second best control is coconut (mesh) nets followed by natural treatment, and mulch method application. Based on its function to reduce the amount of surface water flow known that mulch is a method that produces a largest surface flow.